2023
DOI: 10.3390/math11020477
|View full text |Cite
|
Sign up to set email alerts
|

A New Fuzzy Reinforcement Learning Method for Effective Chemotherapy

Abstract: A key challenge for drug dosing schedules is the ability to learn an optimal control policy even when there is a paucity of accurate information about the systems. Artificial intelligence has great potential for shaping a smart control policy for the dosage of drugs for any treatment. Motivated by this issue, in the present research paper a Caputo–Fabrizio fractional-order model of cancer chemotherapy treatment was elaborated and analyzed. A fix-point theorem and an iterative method were implemented to prove t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 90 publications
0
1
0
Order By: Relevance
“…The identified algorithms primarily aided in the dose individualization of anticoagulants, immunosuppressants and antibiotics [1–5]. In oncology, most of the studies we identified used reinforcement learning, including classical Q-Learning [69], deep Q-Learning [10, 11], deep double Q-Learning [12], fuzzy reinforcement learning [13, 14], conservative Q-Learning [15] and other approaches [16, 17]. Recently, several models have been proposed using neural networks for the prediction of drug concentrations [4, 18–20].…”
Section: Introductionmentioning
confidence: 99%
“…The identified algorithms primarily aided in the dose individualization of anticoagulants, immunosuppressants and antibiotics [1–5]. In oncology, most of the studies we identified used reinforcement learning, including classical Q-Learning [69], deep Q-Learning [10, 11], deep double Q-Learning [12], fuzzy reinforcement learning [13, 14], conservative Q-Learning [15] and other approaches [16, 17]. Recently, several models have been proposed using neural networks for the prediction of drug concentrations [4, 18–20].…”
Section: Introductionmentioning
confidence: 99%